The understanding of intentionality in children with Williams syndrome and Down syndrome - Hahn, Laura J., author; Most, David, advisor; Fidler, Deborah, advisor; Balgopal, Meena, committee member; Lunkenheimer, Erika, committee member (Colorado State University. Libraries, 2012)
This dissertation examined the development of the understanding of intentionality in two different neurogenetic disorders, Williams syndrome (WS) and Down syndrome (DS). The study of intentionality focuses on how children come to understand the intentions of others. Meltzoff's (1995) behavioral reenactment paradigm is a nonverbal procedure wherein a child is presented with a series of objects. Prior to each presentation, the examiner either performs a successful action (e.g. the target action) or an unsuccessful action (e.g. the failed intentional action). A child's understanding of intentionality is assessed by their ability to interpret the experimenter's intention during failed attempt trials, and their subsequent completion of the task. This examination of intentionality was divided into two studies. Study 1 was designed to test Tager-Flusberg and Sullivan's (2000) hypothesis that there is a dissociation between social-perceptual abilities and social-cognitive abilities in individuals with Williams syndrome. In order to explore this dissociation, the behavioral reenactment procedure was administered with and without experimenter affective cues. Participants were 25 children with a confirmed diagnosis of WS. There were two groups of WS, one that received affective cues (N=13) and one that did not (N=12). Also, children with WS in the no affect group were compared to 12 mental-age matched children with developmental disabilities. The findings of this study indicates that the understanding of intentionality improves with developmental status in children with WS. Also, this study indicates that there may be a dissociation between social-perceptual and social-cognitive skills in this population during early social-emotional development. Specifically, it seems that the presence of emotional cues during intersubjective tasks leads to an emotional response instead of a response based on social cognition. Study 2 was motivated by past research suggesting that children with DS demonstrate deficits in some aspects of social cognition, even though many children with DS have strengths in other aspects of social-emotional functioning. Therefore, it is likely that the understanding of intentionality in children with Down syndrome may be influenced by other foundational cognitive abilities (i.e. joint attention and affect sharing in early childhood and executive functioning in middle childhood). Participants were 40 children with a confirmed diagnosis of Down syndrome, 16 young children with DS and 24 older children with DS. In addition, the 16 young children with DS were compared to 16 mental-age matched children with other developmental disabilities. The results of this study suggests that the understanding of intentionality improves with developmental status for young children with DS. This study also suggest that difficulties in joint attention and EF lead children with DS to miss the target relevant information during the behavioral reenactment procedure leading them to perform more "other actions". This dissertation is the first study to examine the development of intentionality in WS and DS. From these studies, it may be possible to begin to characterize how the understanding of intentionality develops in children with WS and DS. Characterizing social cognition in WS and DS will help to identify areas for targeted intervention to prevent the possible cascading effects of difficulties in social cognition on other aspects of development.
Keywords: developmental disabilities; intentionality; social cognition; theory of mind; Down syndrome; Williams syndrome